Insulinoterapia, controle glicêmico materno e prognóstico perinatal - Diferença entre o diabetes gestacional e o clínico - Basso, Neusa Aparecida de Sousa [UNESP]; Costa, Roberto Antonio de Araújo [UNESP]; Magalhães, Cláudia Garcia [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP] (FapUNIFESP (SciELO), 2007)
PURPOSE: to evaluate the insulin therapy protocol and its maternal and perinatal outcome in patients with clinical or gestational diabetes in a high risk reference service. METHODS: descriptive and prospective study including 103 pregnant women with gestational or clinical diabetes treated with insulin and attended by the reference service from October 2003 to December 2005. Gemellarity, miscarriages, unfinished prenatal care and deliveries not attended by the service were excluded. The gestational age at the beginning of the treatment, dosage, doses/day, increment of insulin (UI/kg), glycemic index (GI) and perinatal outcomes were compared. ANOVA, Fisher's exact test and Goodman's test considering p<0.05 were used. RESULTS: multiparity (92 versus 67.9%), pre-gestational body mass index (BMI) >25 kg/m 2 (88 versus 58.5%), weight gain (WG) <8 kg (36 versus 17%) and a high increment of insulin characterized the gestational diabetes. For the patients with clinical diabetes, despite the highest GI (120 mg/dL (39.2 versus 24%)) at the end of the gestational period, insulin therapy started earlier (47.2 versus 4%), lasted longer (56.6 versus 6%) and higher doses of insulin (92 versus 43 UI/day) were administered up to three times a day (54.7 versus 16%). Macrosomia was higher among newborns from the cohort of patients with gestational diabetes (16 versus 3.8%), being the only significant neonatal outcome. There were no neonatal deaths, except for one fetal death in the cohort of patients with clinical diabetes. There were no differences in the other neonatal complications in both cohorts, and most of the newborns were discharged from hospital up to seven days after delivery (46% versus 55.8%). CONCLUSIONS: the analysis of these two cohorts has shown differences in the insulin therapy protocol in quantity (UI/day), dosage (UI/kg weight) and number of doses/day, higher for the clinical diabetes cohort, and in the increment of insulin, higher for the gestational diabetes cohort. Indirectly, the quality of maternal glycemic control and the satisfactory perinatal outcome have proven that the treatment protocol was adequate and did not depend on the type of diabetes.
Insulinotherapy, maternal glycemic control and perinatal prognosis - Difference between clinical and gestational diabetes
Keywords: Blood glucose/analysis; Diabetes mellitus; Diabetes, gestational; Insulin/administration & dosage; Insulin/therapeutic use; Pregnancy; Prognosis